Implementasi Kamera Thermal pada Raspberry pi 3 untuk Pemantauan Suhu Mahasiswa Universitas Kristen Petra - Andre Cristo Singgih; Silvia Rostianingsih; Resmana Lim (Universitas Kristen Petra, 2022)
During the COVID-19 pandemic, face-to-face learning has certain conditions so that the health of both teachers and students remains healthy. One way of prevention at Petra Christian University (PCU) is to check the temperature when entering the campus area. However, manually checking the temperature and looking at the campus access permit made several students or lecturers queue because the security had not finished seeing the campus access permit or checking the temperature of the first visitor who came.For this reason, if there is a program that is able to recognize students and check student temperatures, it will help to expedite the checking process at PCU. The author tries to implement a thermal camera and RFID scanner on a raspberry pi 3 mini computer to be used as a tool that can recognize students through the student identity card and to check student temperatures. In addition, data from checking can be stored in the database to view the records according to the checking information obtained.The results of the system test show that the implementation of the thermal camera and RFID scanner is able to read student identity card and check student temperatures. However, when checking the temperature, the camera has problems when several objects are caught on the screen. Such as the presence of other person or other object such as student’s carrying items that contain hot temperatures. This causes the system to record the temperature of the object that has the hottest temperature in front of the camera screen, this can cause information errors in the checking process.